Students’ English Presentation Skills at Kaung Su Wai English Language Center in Yangon, Myanmar: English - Ven, Withuta; Kanokkamalade, Asst.Prof.Dr.Veerakarn (วารสารพุทธอาเซียนศึกษา, 2025)
This study entitled “Students’ English Presentation Skills at Kaung Su Wai English Language Center in Yangon, Myanmar” aims 1. To study the English presentation skills of students at Kaung Su Wai English Language Centre in Yangon, Myanmar, and 2. To propose the solutions to English presentation skills problems of students at Kaung Su Wai English Language Centre. A mixed-methods research design was employed, incorporating both quantitative and qualitative approaches. Data were collected through questionnaires administered to 51 students and in-depth interviews conducted with five teachers. The findings indicated that students encounter various challenges in English presentations, including a lack of authenticity, poor structural organization, hesitation, time management difficulties, and pronunciation and grammatical errors. Furthermore, nervousness and a fear of speaking negatively can impact their performance. Addressing these challenges through structured guidance, targeted practice, and confidence-building measures can significantly enhance students’ presentation skills. This study underscored the importance of developing students’ English language skills comprehensively. Effective training and positive early experiences can enhance students' confidence and motivation, ultimately contributing to their academic and professional success.